Upgrading to Red Hat Enterprise Linux (RHEL) 8 (Pearson, 2019)
"In Upgrading to Red Hat Enterprise Linux (RHEL) 8 LiveLessons you learn about the new features in Red Hat Enterprise Linux 8, starting with software modules and new storage-related features. This course explains Cockpit, crypto-policies, and LUKS decryption, including how to authorize access to encrypted devices if they are offered on a trusted network. Through demos and whiteboard discussion, these features are explained along with nftables, the drop-in replacement for the iptables firewall solution. The course also discusses how Red Hat Enterprise Linux 8 has become an operating system that focuses on working with containers. The final three lessons dive into the management of containers with podman, and how to manage container images with buildah."--Resource description page